The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/hcr/hqab001
|View full text |Cite
|
Sign up to set email alerts
|

Pornography and Sexual Dissatisfaction: The Role of Pornographic Arousal, Upward Pornographic Comparisons, and Preference for Pornographic Masturbation

Abstract: Research finding that pornography use is associated with lower sexual satisfaction is common; evaluation of the mechanisms hypothesized as underlying the association is not. Informed by multiple theoretical perspectives, the present study tested a conceptual model positing that (a) regularly consuming pornography conditions the user’s arousal template to be particularly responsive to pornographic depictions, (b) this amplified arousal to pornography increases both (c) upward comparisons between one’s own sex l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 71 publications
0
15
1
1
Order By: Relevance
“…Despite previously reported (Miller et al, 2019;Sommet & Berent, 2022; P. J. Wright et al, 2021) detrimental effects of porn use on sexual performance and satisfaction, no such associations were found in the presented study. However, it is important to note that the GFQ-58 sexual dysfunctions scale contains only 2 items and is the second weakest of the whole questionnaire (Styla & Kowalski, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…Despite previously reported (Miller et al, 2019;Sommet & Berent, 2022; P. J. Wright et al, 2021) detrimental effects of porn use on sexual performance and satisfaction, no such associations were found in the presented study. However, it is important to note that the GFQ-58 sexual dysfunctions scale contains only 2 items and is the second weakest of the whole questionnaire (Styla & Kowalski, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…On the one hand, existing research reveals that porn can be a source of sexual inspiration that reinforces sexual permissiveness norms and widens the range of sexual practices and behaviors (Häggström-Nordin et al, 2009; Weinberg et al, 2010; Wright, Bae, & Funk, 2013). On the other hand, the existing research reveals that porn can also be a source of threatening upward sexual comparisons, particularly for men (Wright et al, 2021). For instance, the frequency of porn use predicts penis size dissatisfaction among men (whereas it does not predict genitalia/breast dissatisfaction among women; Cranney, 2015; but see Wright et al, 2017), and it predicts performance-related cognitive distraction during sexual activity among men (but not among women; Goldsmith et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To give a concrete example, because men have a higher sex drive than women, they may derive particular sexual guidelines from porn such as cutting foreplay, which may in turn lead to sexual callousness and erosion of relationship intimacy (for relevant research, see Bridges & Morokoff, 2011; Štulhofer, Buško, & Landripet, 2010a; see also Wright & Vangeel, 2019). In the same vein, men using porn may be more prone to developing sexual performance-related concerns from comparison to the actors and/or feel disappointed in their partner's inability (or lack of desire) to perform the sexual acts portrayed in porn (for relevant research, see Leonhardt & Willoughby, 2019; Sun, Bridges, Johnson, & Ezzell, 2016; Wright, Paul, Herbenick, & Tokunaga, 2021).…”
mentioning
confidence: 99%
“…In regards to adults, prior research has found that those who do not use pornography report the highest sexual satisfaction, particularly surrounding their satisfaction with their sexual partner and the amount of sexual activity they regularly engage in [41]. Although we reviewed evidence above suggesting that using pornography with a partner increases partnered sexual functioning, other research has shown that most pornography users typically consume pornography for the purposes of solitary masturbation, which is associated with decreased sexual satisfaction for both men and women [42][43][44][45][46]. Similarly, it seems that pornography is, at times, associated with preferences for pornographylike sexual encounters, which is, in turn, associated with lower sexual satisfaction [46].…”
Section: Pornography Use and Psychosocial Sexual Functioningmentioning
confidence: 91%